Rola środków społecznego przekazu w budowaniu jedności Europy w refleksji Jana Pawła II - Nawrot, Anna (Annales. Etyka w Życiu Gospodarczym, 2009)
John Paul II emphasized the role of culture in the process of integration in Europe. It is culture and values that allow to find and strengthen the common identity of Europe. John Paul II believed them to be more important than economics and institutional ways of integration. Mass media play the important part in today’s culture. The press, radio, television and other electronic media are sources of knowledge, places for exchanging ideas and sharing experiences. The most important collocations of media in papal thought are: service (duty), responsibility, dialogue and formation. Media should serve people by showing them the objective truth, defending human rights, promoting freedom, justice, solidarity and peace. The responsibility of mass media concerns reliability and integrity, care for customers, especially young and disdained. Dialogue, as John Paul II perceived it, has several dimensions: exchanging ideas and finding the best way of development, sharing experiences and abolishing discriminatory stereotypes, ecumenical and inter-religious meetings. Those assignments should be conducted by personal development of a journalist, which includes professional skills and formation: ethical and spiritual, courage and wisdom. John Paul II saw a great role of social communication in the process of integration, especially in the important task of uniting Europe. The truth and dialogue provided by responsible and reliable media should help people abolish the walls in people’s hearts and establish united Europe open to all inhabitants, who differ but are connected by love, values and culture.